Penerapan Sistem Akuntansi Penjualan Berbasis Desktop Pada Tonggi Coffe Surabaya - Rudi Pratono; Magdalena Irma Panjaitan (LPPM Universitas Wijaya Kusuma Surabaya, 2024)
The aim of this research is to analyze the planning of a desktop-based sales system at Tonggi Coffee in handling sales transactions. This thesis also not only designs but also implements applications so that it can overcome the company's problems, namely the lack of synchronization between data in the field and reports made. In this research, the researcher uses a descriptive method, the type of data used is secondary data. Data collection techniques in this research are by means of interviews, observation and documentation. The results of this research show that the company has problems in recording sales due to frequent employee changes and recording or sales made not based on employee job desks, resulting in inappropriate data. Therefore, researchers provide solutions by implementing computerized applications to overcome problems in companies